Enhanced and Durable Light‐Driven Hydrogen Evolution by Cobalt‐Based Prussian Blue Analogs in Phospholipid Bilayers - Subrata Mandal; Akash Deshpande; Robert Leiter; Johannes Biskupek; Ute Kaiser; Andrea Pannwitz (Advanced Energy & Sustainability Research)
Light‐driven hydrogen (H2) evolution in water is performed using a series of cobalt‐based Prussian blue analogs (MCo PBAs) with MII3[CoIII(CN)6]2, M = Co, Ni, Cu, Zn embedded in phospholipid bilayers with the amphiphilic ruthenium‐based photosensitizer RuC9. Hydrophobic surface functionalization of MCo PBA nanoparticles with oleylamine facilitates close proximity of the PBA to the photosensitizer within lipid bilayers of vesicles, enhancing photocatalytic performance. The type of metal and rigidity of the lipid environment significantly influences hydrogen evolution reaction efficiency, with the trend: Ni > Co > Zn > Cu and DMPC > DOPC > DPPC. Among these, NiCo PBA in DMPC: (14:0 PEG2000 PE) vesicles shows the highest efficiency, with a ninefold increase in H2 production compared to the conventional aqueous system. This sustained activity is attributed to the efficient electron transfer and the scaffold's stability. This study provides valuable insights for the development of scalable and cost‐effective photocatalytic technologies.